Relationship of summer gains of yearling steers on bluestem pastures with feeder grade, shade of color, weight at the start of the grazing season and previous winter gain. - Holland, L.A.; Wheat, J.D.; Smith, E.F.; Smith, W.H.; Good, D.L.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
Feeder grade, shade of color, and weight are some factors considered by cattlemen who purchase or produce yearling steers to pasture. The objective of this study is to determine the relationship of summer gains of yearling steers on bluestem pastures with feeder grade. shade of color, weight at the start of the grazing season and previous winter gain.
Keywords: Beef; Gain; Bluestem pasture; Grade; Color